Evaluation of the organizational climate of the teaching staff of the Higher Education Institutions (HEIs) of the Province of Chimborazo - Ecuador - Baño Ayala, Darío Javier (2016)
The investigation arose from the need to identify whether the organizational climate in academics is favorable or not to carry out their academic activities; at which a methodology was developed to measure the organizational climate in the IES of the province of Chimborazo, using a survey validated by Chiang et al. (2008); a sample of 319 teachers; then the reliability of the instrument was determined by Cronbach's alpha coefficient (α = 0.914), the Exploratory Factor Analysis AFE (KOM = 0.962) in order to determine the validity of the construct of organizational climate was applied which led to a regrouping in four final dimensions: 1. Support and Innovation Trust (TCL_ACI), 2. Recognition and Equity (TCL_ER), 3. Autonomy (TCL_AUTO) and 4 Cohesion (TCL_COHO); then it estimated by the least squares method unweighted MIMIC model determined a positive association of all these dimensions on climate latent variable structural equation was obtained; finally a comparative study of organizational climate between the Polytechnic School of Chimborazo (ESPOCH) and National University of Chimborazo (UNACH) was performed.